2013
DOI: 10.1097/sla.0b013e3182777fa4
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the World Health Organization Surgical Safety Checklist, Including Introduction of Pulse Oximetry, in a Resource-Limited Setting

Abstract: Successful hospital-wide Surgery Safety Checklist implementation can be achieved in a resource-limited setting and can significantly reduce surgical hazards and complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 18 publications
2
115
1
4
Order By: Relevance
“…[16] To date only Haynes et al [4] have shown significant reductions in mortality, other studies having failed to do so. [2,[5][6][7][8] The overall complication rates in our study were lower than those reported by others. [4,5,7] This may be because previous studies were done in tertiary, central or specialised teaching hospitals on highrisk patients, and we specifically excluded such hospitals.…”
Section: Other Findingscontrasting
confidence: 54%
See 1 more Smart Citation
“…[16] To date only Haynes et al [4] have shown significant reductions in mortality, other studies having failed to do so. [2,[5][6][7][8] The overall complication rates in our study were lower than those reported by others. [4,5,7] This may be because previous studies were done in tertiary, central or specialised teaching hospitals on highrisk patients, and we specifically excluded such hospitals.…”
Section: Other Findingscontrasting
confidence: 54%
“…[3] Haynes et al [4] showed reductions in the death rate of between 1.5% and 0.8% in their study in eight different hospitals globally. In addition, while many investigators have demonstrated statistically significant reductions in postoperative complications after implementation of the SSCL, [4][5][6][7] others have not found the same benefits. [2,8] Very few studies from low-and middle-income countries (LMICs) have measured the impact of the SSCL on maternal mortality, despite surgical mortality being reported to be five to ten times higher than in high-income countries (HICs), and the rate of deaths due to general anaesthesia being as high as 1 per 150 cases in some parts of sub-Saharan Africa.…”
Section: Researchmentioning
confidence: 99%
“…Following Haynes's study, (9) others were published (19)(20)(21) showing improvements in the care outcomes, culminating in a meta-analysis that demonstrated a 43% reduction in the risk of surgical infection (RR 0.57, CI 0.41-0.79 ) with the use of the checklist. (10) A systematic review (13) published in 2016, involving 25 studies, demonstrated reduction of complications, mainly in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…1 Dr Gawande conducted a multinational study to determine how effective a 19-item Surgical Safety Checklist could be in improving outcomes. 2 Although each site had to make accommodations for their local conditions, every site that implemented the checklist saw decreased complications and mortality. Dr Gawande's other studies have focused on checklists that can be used in the operating room, childbirth, and for hospital-acquired infections.…”
Section: To Check or Not To Check: The Role Of Checklists In Childrenmentioning
confidence: 99%